Exercise and anemia in cancer patients: could it make the difference?. Issue 11 (2nd November 2021) - Avancini, Alice; Belluomini, Lorenzo; Tregnago, Daniela; Trestini, Ilaria; Milella, Michele; Lanza, Massimo; Pilotto, Sara
ABSTRACT: Introduction: Anemia is one of the most common hematological manifestations occurring in cancer patients, related to a poorer prognosis. Among supportive care in cancer, exercise is emerging as a crucial tool demonstrating reduction in mortality risk and counteracting several diseases and treatment-related adverse events. Nevertheless, the effect of exercise on anemia in cancer is still a relatively unexplored area. Area covered: Six studies investigated the impact of exercise on anemia trajectory in cancer patients, with intriguing results. The potential mechanisms by which exercise may modulate the blood system are heterogenous, including bone marrow stimulation, improvements in the hematopoietic microenvironment, and control of both inflammation and hormone levels. Although training and/or living at high altitudes is a recognized method to increase erythropoiesis, the effect of a hypoxic external environment on tumor progression should be clarified before considering this strategy in cancer patients. Expert opinion: Although the available investigations of exercise in anemic patients with cancer are few, exercise emerges as an important supportive oncological care capable of assisting patients in maintaining their autonomy. Our special report offers several suggestions to address future research in this field and determine the real contribution of an active lifestyle on this condition.